7x=9-3(x-1)

Simple and best practice solution for 7x=9-3(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x=9-3(x-1) equation:


Simplifying
7x = 9 + -3(x + -1)

Reorder the terms:
7x = 9 + -3(-1 + x)
7x = 9 + (-1 * -3 + x * -3)
7x = 9 + (3 + -3x)

Combine like terms: 9 + 3 = 12
7x = 12 + -3x

Solving
7x = 12 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
7x + 3x = 12 + -3x + 3x

Combine like terms: 7x + 3x = 10x
10x = 12 + -3x + 3x

Combine like terms: -3x + 3x = 0
10x = 12 + 0
10x = 12

Divide each side by '10'.
x = 1.2

Simplifying
x = 1.2

See similar equations:

| (x-3)2=(3x-5)2 | | (27.9-18.6)/3.1 | | 3.5=14 | | (x-3)-(5-3x)=2x(x+1) | | 6x-3+x-4=4x+5+3x | | 2x^2+(2-i)x+1=0 | | 25y^2-100x^2=0 | | v^2+2v+7=0 | | 5n^2=90-15n | | 35-2r=3r-5 | | z+3=29*2 | | 18-2x^2/9-3x | | -196=-9.8t^2 | | -1.8=-5x-8 | | 6x^2-5x-9=0 | | f(x)=8x+11 | | ln(9x^2-4)=6x+4 | | -5xy^4(4xy^2+7xy-8x)= | | x-x*sqrt(3)=100 | | kx^2-kx+9=0 | | 12(7/3) | | 22,25/0,555 | | 22,25-/0,555 | | (3x+2)=360 | | (4x-4)=360 | | 2t^5= | | 0,9/x=100/1000 | | 6x^4+4x^2-2=0 | | 15/x=20/40 | | 4x+39-6x=1-9x+3 | | 6x^3-5x^2-3x+2=(x-1)(ax^2+bx+c) | | 7/x=30 |

Equations solver categories